LITERATURE STUDY: STUDENTS' CURIOSITY ABOUT STEM-PBL MODEL IN SCIENCE CLASSROOM - Putri, Dara Adinda; Zahra, Fathia (Pendidikan IPA, FMIPA, UNP, 2024)
Problem Based Learning (PBL) is a form of problem-based learning that is given to students to apply knowledge to issues or problems as a form of problem solving. Its integration with the STEM (Science, Technology, Engineering, and Mathematics) approach can train students to apply their knowledge in making designs as a form of problem solving related to the environment using technology. The purpose of writing this article is to find out the improvement, response and impact of students' curiosity by using the STEM-PBL learning model in science class. The method used is content analysis, with the principles of Preferred Reporting Items For Systematic Reviews and Meta Analysis (PRISMA). Based on the results of this study, it shows that students' curiosity towards STEM PBL in science classes shows significant results overall because the application of hands-on activities as a learning strategy is able to form various skills and provide positive results and even increase.